Modeling and Measurement Methods for Acoustic Waves and for Acoustic Microdevices - Beghi, Marco G. (IntechOpen, 2013)
Acoustics is a mature field which enjoys a never ending youth. New developments are induced by either the search for a better understanding, or by technological innovations. Micro-fabrication techniques introduced a whole new class of microdevices, which exploit acoustic waves for various tasks, and in particular for information processing and for sensing purposes. Performance improvements are achievable by better modelling tools, able to deal with more complex configurations, and by more refined techniques of fabrication and of integration in technological systems, like wireless communications. Several chapters of this book deal with modelling and fabrication techniques for microdevices, including unconventional phenomena and configurations. But this is far from exhausting the research lines in acoustics. Theoretical analyses and modelling techniques are presented, for phenomena ranging from the detection of cracks to the acoustics of the oceans. Measurement methods are also discussed, which probe by acoustic waves the properties of widely different systems.